PELATIHAN TARI LEGONG SEMARANDANA GAYA PELIATAN OLEH NI KETUT PUTRI MINANGSARI DI WULANGREH OMAH BUDAYA - Ida Ayu Julia Maharani; Ida Bagus Ketut Sudiasa; Sulistiani (Jurnal Pendidikan Tari, 2025)
This research was compiled by Ida Ayu Julia Maharani with the title "Legong Semarandana Dance Training Style Peliatan by Ni Ketut Putri Minangsari at Wulangreh Omah Budaya". This research is the preservation of traditional Balinese dances, especially Legong Semarandana in the Peliatan style, outside the area of origin. The training conducted showed a unique and authentic training strategy at Wulangreh Omah Budaya, South Jakarta. The purpose of this study is to explain the process and results of the training of the Peliatan style Legong Semarandana dance carried out by Ni Keut Putri Minangsari, there are methods, strategies and design of training and examine the effectiveness of training in forming skills. This study uses a descriptive qualitative approach. Data collection was carried out through direct observation of the training process, interviews with trainers and students, and documentation. Data analysis was carried out with reference to training theory by Dale S. Beach and the principles according to kamil. The results of the study show that the training is carried out in a structured and tiered manner based on the level of students' ability. The superior strategy in the form of direct training in Peliatan village has a great impact on technique and character appreciation. Evaluations are carried out periodically to improve performance. This research proves that the training conducted by Ni Ketut Putri Minangsari is effective in preserving the Peliatan style Legong Semarandana outside Bali.